Evaluation of Pound concept in determination of mediolateral mandibular posterior teeth position - Majid Naser Khaki; Maryam Mohajerfar; Masood Ejlalai; Sara Tvakolizadeh (Mashhad University of Medical Sciences, 2017)
Background: The ideal teeth arrangement is an important step for success in complete denture fabrication. There are different methods for determining the posterior denture teeth location. The purpose of this study was the comparison of posterior mandibular teeth location in the study group with Pound or Misch theory. Material and methods: An alginate mandibular impression of 80 dentate patients was taken and poured with dental stone. Retromolar pad area, mesial of canine and the lingual cusps of each posterior tooth marked on the cast and then transferred to the graded paper. Distance of each lingual cusp from the internal line of Pound triangle was measured. Data were analyzed with SPSS version 16.0. Result: In the study group, the average distance of lingual mandibular cusp from the internal line of Pound triangle was 1.69 mm in first premolars, 0.94 mm in second premolars, 0.7 mm in first molars and 0.75 mm in second molars. Conclusion: In most cases, distance of lingual mandibular cusps was within 1 mm of Pound triangle. Results were more similar to the Pound rather than the Misch theory.